Fennoscandian freshwater control on Greenland hydroclimate shifts at the onset of the Younger Dryas - Muschitiello, Francesco; Pausata, Francesco S. R.; Watson, Jenny E.; Smittenberg, Rienk H.; Salih, Abubakr A. M.; Brooks, Stephen J.; Whitehouse, Nicola J.; Karlatou-Charalampopoulou, Artemis; Wohlfarth, Barbara (Nature Communications, 2015)
Abstract Sources and timing of freshwater forcing relative to hydroclimate shifts recorded in Greenland ice cores at the onset of Younger Dryas, ∼12,800 years ago, remain speculative. Here we show that progressive Fennoscandian Ice Sheet (FIS) melting 13,100–12,880 years ago generates a hydroclimate dipole with drier–colder conditions in Northern Europe and wetter–warmer conditions in Greenland. FIS melting culminates 12,880 years ago synchronously with the start of Greenland Stadial 1 and a large-scale hydroclimate transition lasting ∼180 years. Transient climate model simulations forced with FIS freshwater reproduce the initial hydroclimate dipole through sea-ice feedbacks in the Nordic Seas. The transition is attributed to the export of excess sea ice to the subpolar North Atlantic and a subsequent southward shift of the westerly winds. We suggest that North Atlantic hydroclimate sensitivity to FIS freshwater can explain the pace and sign of shifts recorded in Greenland at the climate transition into the Younger Dryas.